The intersection of learning difficulties and behavior problems – a scoping review of intervention research - Gabriel, Taina; Börnert-Ringleb, Moritz (Frontiers in Education, 2023)
Learning difficulties (LDif) and behavioral problems (BP) frequently co-occur. Affected students typically require interventions targeting learning-, social-, as well as emotional and behavioral-domains. The goal of this scoping review is therefore to provide an overview of the research on interventions that target these critical areas for students with or at-risk of disabilities. In total, 48 relevant studies were identified and analyzed regarding addressed competencies, target groups, the setting of the interventions as well as underlying causal assumptions. The review identified a variety of interventions and approaches designed to address LDif and BP, which makes it impossible to draw conclusions on a single best approach. Co-occurring LDif and BP reflect a plurality of difficulties that are incompatible with a 'one size fits all' approach. The vast majority of studies assumed that the relationship between LDif and BP are reciprocal/unidirectional. Few studies focused common variables that potentially affect both LDif and BP. In addition, the majority of studies addressed child-level variables. Future research should be conducted to focus on variables at the environmental or institutional level that might impact both LDif and BP.